2019
DOI: 10.3390/gels5010015
|View full text |Cite
|
Sign up to set email alerts
|

Designing Supramolecular Gelators: Challenges, Frustrations, and Hopes

Abstract: This article is a personal account of the author, who serendipitously entered the field of supramolecular gels nearly two decades ago. A supramolecular synthon approach in the context of crystal engineering was utilized to develop a working hypothesis to design supramolecular gelators derived from simple organic salts. The activity not only provided a way to occasionally predict gelation, but also afforded clear understanding of the structural landscape of such supramolecular materials. Without waiting for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…A recent study on the possibility of developing a general road map to an ab initio design of a gelator or a gel, has demonstrated that is not possible to achieve such a goal, as more molecular-level insights into the self-assembly process leading to gelation are required [19,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on the possibility of developing a general road map to an ab initio design of a gelator or a gel, has demonstrated that is not possible to achieve such a goal, as more molecular-level insights into the self-assembly process leading to gelation are required [19,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…[306][307][308] Generally, the binding sites are connected to some associating units on the gelator structure that assist self-assembly involving non-covalent interactions. 18,[309][310][311] Such associating units may contain hydrophobic moieties like cholesterol 169,[312][313][314] and aromatic surface, 315 or hydrophilic functionalities like peptide, 316 sugar 317 etc. Chemical analyte responsive gels have huge potential as molecular sensors, aggregation probes, antibacterial agents, conducting materials and water purifying agents.…”
Section: (Vii) Post Assembly Fabrication Of Gels By Chemical Analytesmentioning
confidence: 99%
“…Supramolecular gels are formed when monomeric building blocks self-assemble into long fibrous structures that entrap solvent molecules. [1][2][3][4][5][6][7] Generally, man-made selfassembly is an energetically down-hill process and so selfassembled gels can be formed under thermodynamic equilibrium. [8][9][10][11] However, depending on the preparative pathway, self-assembled gels may exist as kinetically trapped structures where the assembly structures reside in the local thermodynamic minimum in the free energy landscape.…”
Section: Introductionmentioning
confidence: 99%